PENERAPAN METODE REWARD AND PUNISHMENT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD NEGERI 28 KOTA TERNATE PADA SUB TEMA 2 PERUBAHAN LINGKUNGAN - Putri Amelia Buamona; Pamuti Pamuti; Selvi Wulandari (PEDAGOGIK, 2023)
The aims of this study were (1) to find out the application of the Reward and Punishment method to improving the learning outcomes of fifth grade students at SD Negeri 28 Ternate City in sub-theme 2 about environmental change (2) to find out the improvement in learning outcomes for fifth grade students at SD Negeri 28 Ternate City towards the application of the Reward and Punishment method to Sub-Theme 2 of Environmental Change. This research is Classroom Action Research (PTK) which consists of 3 stages including (1) Planning (2) Implementation and observation (3) Reflection. This research was conducted at SD Negeri 28 Kota Ternate class V with a total of 17 students consisting of 11 boys and 6 girls. Data collection techniques used in this study were observation, documentation and written tests. Data analysis used in this research is qualitative analysis.Based on the results of the study, it was shown that in cycle I there were 11 or 64.70% of students who achieved the KKM score. This shows that with the application of the Reward and Punishment method to improve the learning outcomes of fifth grade students at SD Negeri 28 Kota Ternate in sub-theme 2 environmental change has not been successful. Therefore this action is continued in cycle II. With the improvement in cycle II there was an increase in learning outcomes, namely 14 or 82.35% of students who had achieved KKM scores were obtained. Thus it can be concluded that with the application of the Reward and Punishment method to improve student learning outcomes of class V SD Negeri 28 Ternate City in sub-theme 2 environmental change can improve student learning outcomes and be declared successful.